Aspek Hukum Hidup Bersama Sebagai Suami Isteri Tanpa Ikatan Perkawinan - Gugu, Steven S. (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The public's reaction to the act of social deviation, gathering together often reaps various negative responses and tends to be vigilante (eigenrichting). Based on this, it is necessary that the act of gathering together is categorized as a crime through a criminalization policy. The Draft Criminal Code has listed this act as a crime of decency, but in its formulation it needs to be re-examined regarding its impact on society. This study aims to provide an analysis of the extent to which the criminalization of gathering kebo brings social impacts to the community. This research is a normative legal research with a conceptual approach. The data collection technique was carried out by literature study, namely studying primary legal materials and secondary legal materials. The analysis used in this research is prescriptive, to find out what should be done to answer the legal issues raised in this paper. The result of this research is that the criminalization of the act of gathering together needs to consider the social aspects of society.